Analysis of Work Experience, Competence and Job Satisfaction on Employee Performance at Bank Sumut Head Office - Ikhsan Alkhairi; Ikhah Malikhah (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of work experience, competence, and job satisfaction on employee performance at the Head Office of Bank Sumut. The research employed a quantitative approach with a causal research design. The population consisted of all employees in the Human Resources Division of Bank Sumut Head Office, with a saturated sampling technique applied. Primary data were collected through questionnaires, while secondary data were obtained from literature reviews. Data analysis methods included validity and reliability tests, classical assumption tests, and multiple linear regression analysis, with hypothesis testing conducted using t-test and F-test. The results indicate that, partially, work experience and competence do not have a significant effect on employee performance, whereas job satisfaction has a significant effect. However, simultaneously, work experience, competence, and job satisfaction have a significant influence on employee performance. These findings suggest that job satisfaction plays a dominant role in improving employee performance, while work experience and competence contribute when considered jointly.